Epilepsy: a cross‐sectional study of paediatricians and general practitioners on their experiences, knowledge and handling of the disease. Issue 2 (30th April 2019) - Schnabel, Sabrina; Neininger, Martina Patrizia; Bernhard, Matthias Karl; Merkenschlager, Andreas; Kiess, Wieland; Bertsche, Thilo; Bertsche, Astrid
ABSTRACT: Aims : Epilepsy is a life‐changing disease, and patients with epilepsy may face a number of issues. Paediatricians and general practitioners are often the first to be asked for advice. This cross‐sectional study was performed to gain information on the knowledge and experiences of paediatricians and general practitioners on epilepsy. Methods : From September 2015 to July 2017, paediatricians and general practitioners in Leipzig, Germany, were asked to take part in a face‐to‐face interview. Results : Overall, 40 paediatricians and 60 general practitioners participated in the study. A total of 99/100 (99%) kept emergency medication available and 96/100 (96%) would administer it during a seizure. Also, 40/40 (100%) of the paediatricians and 34/60 (57%) of the general practitioners recommended that non‐professionals should administer emergency medication, and 18/40 (45%) of the paediatricians and 35/60 (58%) of the general practitioners would put an object in the patient's mouth during a seizure. With regards to safety precautions, paediatricians mentioned the risks associated with swimming (30/40; 75%) and the potential of falling from a height (23/40; 58%), whereas general practitioners focused on being around vehicles including driving regulations (43/60; 72%). Only 5/60 (8%) of the general practitioners advised that precautions should be taken during swimming. Fatigue/exhaustion was the most common adverse drug event associated with long‐term anticonvulsive therapy mentioned by paediatricians (13/40; 33%) and general practitioners (27/60; 45%). Of all the participants, 23/100 (23%) recommended epilepsy training programmes for patients and families, however, none were able to name a specific programme. Conclusion : Nearly half of the general practitioners did not recommend the use of rescue medication by non‐professionals. This measure, however, can prevent the occurrence of prolonged non‐treatable seizures. Both paediatricians and general practitioners should bear in mind that placing an object in the mouth during a seizure should be avoided due to the risk of additional injury. To reduce the risk of drowning, physicians should recommend safety precautions during swimming. Information on epilepsy training programmes for patients and families should be diffused to all physicians taking care of patients with epilepsy.